PENGARUH UNSUR SINEMATOGRAFI KDRAMA TERHADAP EFEK SINEMATERAPI PADA PEREMPUAN PEKERJA DI DKI JAKARTA - Fitriati, Trimalda Nur; Satrinia, Dwina; Sularso, Alva Nurvina; Rahmayadi, Gagas Ezhar; Azzahrah, Aprilia Putri (Narada : Jurnal Desain dan Seni, 2024)
As economic demands increase and gender roles change, the number of working women increases. The challenges faced by working women are also high, because they need to balance their roles as "housewives" and career women. This resulted in an increasing stress levels in working women. Another way to overcome stress beside getting enough rest is to do enjoyable things, such as doing hobbies or watching films. K-drama has regained its place in the hearts of Indonesian women for their popularity both in storylines and attractive casts. It has elements that can reduce the stress of their viewers. Therefore, this study aims to determine the cinematographic elements of K-dramas that can provide a cinematherapy effect on working women. This study uses both qualitative and quantitative methods. The main data collection was carried out by interviewing female working respondents who live in DKI Jakarta. As a result, the cinematographic element that has the most influence on the cinematherapy effect on K-dramas is the type of shot. According to a number of respondents, types of shots such as medium close up, extreme close up, are able to enhance the dramatic effect from humorous scenes of K-drama.